2021
DOI: 10.2196/28275
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health Training Programs for Medical Students: Scoping Review

Abstract: Background Medical schools worldwide are accelerating the introduction of digital health courses into their curricula. The COVID-19 pandemic has contributed to this swift and widespread transition to digital health and education. However, the need for digital health competencies goes beyond the COVID-19 pandemic because they are becoming essential for the delivery of effective, efficient, and safe care. Objective This review aims to collate and analyze … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 53 publications
(402 reference statements)
3
32
0
Order By: Relevance
“…Countries coming from WHO South‐East Asia region include India, Nepal, Indonesia, Thailand, and Pakistan. Overall, our findings indicate a poor or a lack of an adequate (both in terms of contents and dedicated teaching time) theoretical and practical training in digital psychiatry and related topics disciplines (e.g., e‐health, e‐mental health, telemedicine, telepsychiatry) across different countries here included, which is in line with previous studies (Casà et al, 2021; Cory & Stevens, 2020; Feroz et al, 2021; Jameson et al, 2011; Pinto da Costa et al, 2019; Pote et al, 2021; Tudor Car et al, 2021). However, despite the initial intent was recruiting both LMICs and upper‐middle‐income countries to compare findings and estimate whether WBI may influence the level of training, experience, and knowledge on digital psychiatry, our sample is mainly constituted by six countries, of which only Japan is included in upper‐middle‐income countries, according to the gross national income per capita as published by the World Bank (World Bank Data, 2021).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Countries coming from WHO South‐East Asia region include India, Nepal, Indonesia, Thailand, and Pakistan. Overall, our findings indicate a poor or a lack of an adequate (both in terms of contents and dedicated teaching time) theoretical and practical training in digital psychiatry and related topics disciplines (e.g., e‐health, e‐mental health, telemedicine, telepsychiatry) across different countries here included, which is in line with previous studies (Casà et al, 2021; Cory & Stevens, 2020; Feroz et al, 2021; Jameson et al, 2011; Pinto da Costa et al, 2019; Pote et al, 2021; Tudor Car et al, 2021). However, despite the initial intent was recruiting both LMICs and upper‐middle‐income countries to compare findings and estimate whether WBI may influence the level of training, experience, and knowledge on digital psychiatry, our sample is mainly constituted by six countries, of which only Japan is included in upper‐middle‐income countries, according to the gross national income per capita as published by the World Bank (World Bank Data, 2021).…”
Section: Discussionsupporting
confidence: 86%
“…Participants who studied their psychiatric training program in Japan also reported higher K scores compared to other countries (p = .004). Participants who currently work in Japan telepsychiatry) across different countries here included, which is in line with previous studies (Casà et al, 2021;Cory & Stevens, 2020;Feroz et al, 2021;Jameson et al, 2011;Pinto da Costa et al, 2019;Pote et al, 2021;Tudor Car et al, 2021) to 5, from the least mature to the most mature digitalization process)…”
Section: Level Of Knowledgesupporting
confidence: 75%
“…Some medical schools have implemented digital health courses, although their integration thus far has been heterogenous. In a recent scoping review of digital health courses in medical schools, the authors found that the majority of courses were elective and mainly focused on medical informatics [ 24 ]. They are thus not routinely integrated into the curriculum and tend to focus on narrow topics within digital health.…”
Section: Discussionmentioning
confidence: 99%
“…• Define and test outcomes of the learning success by combining subjective and objective measures based on digital health technology literacy frameworks [58]. However, note that there is a lack of randomized controlled trials in the field because workshops within elective subjects pose organizational and ethical challenges for this particular study design [59].…”
Section: For Researchersmentioning
confidence: 99%